2011
DOI: 10.1111/j.1744-7410.2011.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of the metapleural gland in workers of the ant Crematogaster inflata (Hymenoptera, Formicidae)

Abstract: Abstract. Workers of Crematogaster inflata possess the largest metapleural glands (relative to body size) known among ants, with reservoirs extending anteriorly up to the junction between the pro‐ and the mesothorax, and with over 1400 secretory cells on both sides together. This large secretory capacity is related to the gland's defensive function, which, in members of this species, is directed against larger arthropod and vertebrate enemies, and apparently not against microorganisms, in contrast to other an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
3
14
0
2
Order By: Relevance
“…Since they do not have the purported pressure that soil inhabiting ant species have to produce antimicrobial defenses, their MGs were expected to be non-functional and atrophied (Hölldobler and Engel-Siegel 1985). Instead, their MGs are highly developed; in fact, C. inflata has the largest known MGs (measured by secretory cell counts, Billen et al 2011). Metapleural gland chemistry has been reported for C. difformis in two reports, one using samples collected from Malaysia (Attygalle et al 1989) and the other from Brunei (Jones et al 2005).…”
Section: Crematogastermentioning
confidence: 95%
See 1 more Smart Citation
“…Since they do not have the purported pressure that soil inhabiting ant species have to produce antimicrobial defenses, their MGs were expected to be non-functional and atrophied (Hölldobler and Engel-Siegel 1985). Instead, their MGs are highly developed; in fact, C. inflata has the largest known MGs (measured by secretory cell counts, Billen et al 2011). Metapleural gland chemistry has been reported for C. difformis in two reports, one using samples collected from Malaysia (Attygalle et al 1989) and the other from Brunei (Jones et al 2005).…”
Section: Crematogastermentioning
confidence: 95%
“…When minimum inhibitory concentrations from Kabara et al (1972) are compared with the amount of each of the four carboxylic acids found by Cabrera et al (2004), it is clear that one (S. geminata) or two of the acids (S. invicta) are at a concentration high enough to inhibit bacterial growth (Table 2), especially since the MG reservoir volume is likely much less than 1 μl. The hypertrophied MG reservoir volume for Crematogaster inflata is about 0.1 μl (data in Billen et al 2011).…”
Section: Solenopsis-fire Antsmentioning
confidence: 98%
“…As C. saundersi had higher diversity and quantity of chemicals, including several noxious ones (e. g.: 2,4-dihydroxyacetophenone), than P. furcata, its polyrhachis-furcata spores and also at a similar level to Fungizone. These results are not surprising because the chemical secretion from metapleural glands of ants were largely reported to be antiseptic or antimicrobial (Attygalle et al 1989, Morgan 2008, Billen et al 2011, Yek and Mueller 2011, Vieira et al 2012.…”
Section: Discussionmentioning
confidence: 94%
“…Crematogaster ants have well developed metapleural glands (Attygalle et al 1989;Vander Meer, 2012;Tranter et al, 2015). C. inflata that occurs in Southeast Asia has the largest known metapleural glands (measured by counting secretory cells) (Billen et al, 2011). The amount of secretion produced by the metapleural gland and the greater ease of extraction due to size may justify the number of studies performed with Crematogaster ants.…”
Section: Discussionmentioning
confidence: 99%